THE EFFECT OF LEADERSHIP STYLE, WORK MOTIVATION, AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE AT BADAN PUSAT STATISTIK PROVINSI SULAWESI UTARA - Febiola Feiby Palilingan; David P. E. Saerang; Lawren J. Rumokoy (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
Human resources are the most important factor in running a good company. Human resources play an important role in the ups and downs of company performance. The purpose of this research is to analyze the effect leadership style, work motivation, and career development on employee performance of employee at BPS Provinsi Sulawesi Utara partially and simultaneously. This research conducted using quantitative method with saturation sampling method, which the population are 80 civil employees and for the sample totaling 53 civil employees sample due to a small amount of population. The collected data from questionnaires with Likert scale method was processed in SPSS 25 resulting leadership style, work motivation, and career development are effect employee performance simultaneously, leadership style and career development effect employee performance partially, and work motivation does not affect employee performance partially. In this research, a work motivation does not play an important role because of motivation of employees still less, while leadership style and career development will be considered by employee to increase the performance.   Keywords: leadership style, work motivation, career development, employee performance